Bentuk Tari Munai Serapah di Sanggar Seni Sedulang Setudung Kabupaten Banyuasin (Komponen Nonverbal) - Sari, Mia Julita; NAD, Nugroho; Adoma, Auzy Madona (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this study was to determine and describe the form of Munai Serapah Dance in Sedulang Setudung Art Studio, Banyuasin Regency. The method used in this research is the qualitative method. The data collection techniques in this research are observation, interviews, and documentation. The data analysis technique used is data reduction, data presentation, and conclusion drawing. The results showedthat the body movements in munai serapah dance use basic Malay movements that are developed and created so as to create movements and music that are in harmony without reducing the meaning of the dance conveyed. The floor patterns used in Munai Serapah dance are arrows, circular, angled, straight,